THE EFFECTS ANALYZING OF LOOKING FOR WORD OF MOUTH COMMUNICATION WITH ACTIVE AND BRAND TRUST TO PURCHASE DECISION (CASE STUDY : PT. BAKRIE TELECOM) (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2009)
AbstractThe purpose of this research is to know the effects analyze of looking for word of mouth communication with active and brand trust Based on cased study  in  PT. Bakrie Telecom with the object is Esia phonecellular card. This research have been using to obtain primary data from field research customer PT. Bakrie Telecom and also secondary data that can support of this research. In order to know the impact of independent variable concerning to dependent variable, linear regression anlyze are used in SPSS 12.0 for Windows. The result from research are known that independent variable to dependent variable are have relationship.  T-test are known that looking for word of mouth communication with active are have the significant of relationship to the purcase decision,  eventhough   brand trust do not have the significant  of relationship  to the purchase decision. F-test are known that have relationship between independent and dependent variable. Keywords: Word of Mouth Communication, Brand Trust, Purchase Decision